Laser Frequency Combs with Fast Gain Recovery: Physics and Applications (Laser Photonics Rev. 16(2)/2022). Issue 2 (5th February 2022) - Piccardo, Marco; Capasso, Federico
Abstract : Fast Gain Recovery In article number 2100403, Marco Piccardo and Federico Capasso discuss the history, underlying physical mechanisms, and new perspectives of lasers with fast gain recovery. The review focuses on the most representative example of the class—the quantum cascade laser—and, in particular, its frequency comb regimes, from frequency‐modulated states to harmonic combs to the novel spatiotemporal structures of ring lasers.